2014
DOI: 10.1111/1750-3841.12725
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Flavor and Viscosity in Hot and Cold Break Tomato Juice and Sauce by Peel Removal

Abstract: Tomatoes are typically not peeled before being made into juice but the peels contain enzymes that affect the odor, flavor, and viscosity of the juice. The peels are removed in the finisher, but their presence during the break process may affect quality. Juice was processed from peeled and unpeeled tomatoes using hot or cold break. The juices were pasteurized by high temperature short time (HTST), low temperature long time (LTLT), or with a retort. The control samples were treated with 10% calcium chloride to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In contrast, the concentration of some important volatile compounds (hexanal, E‐2‐hexenal, Z‐3 hexenal and 1‐penten‐3‐one) decreased (Markovic, Vahcic, Ganic, & Banovic, ; Min & Zhang, ; Viljanen et al, ) and some volatiles (E‐2‐hexenal, 2‐methyl butyric acid, 1‐hexenol, Z‐3‐hexenol) were not detected after thermal processing (Markovic et al, ). Mirondo and Barringer () found differences in the volatile profile of tomato juice from cold break and hot break, being at lower quantity in the latter. The same authors observed that after the concentration step the loss of volatiles followed the same pattern irrespective of the previous blanching process.…”
Section: Conventional Thermal Processing As Current Practicementioning
confidence: 99%
“…In contrast, the concentration of some important volatile compounds (hexanal, E‐2‐hexenal, Z‐3 hexenal and 1‐penten‐3‐one) decreased (Markovic, Vahcic, Ganic, & Banovic, ; Min & Zhang, ; Viljanen et al, ) and some volatiles (E‐2‐hexenal, 2‐methyl butyric acid, 1‐hexenol, Z‐3‐hexenol) were not detected after thermal processing (Markovic et al, ). Mirondo and Barringer () found differences in the volatile profile of tomato juice from cold break and hot break, being at lower quantity in the latter. The same authors observed that after the concentration step the loss of volatiles followed the same pattern irrespective of the previous blanching process.…”
Section: Conventional Thermal Processing As Current Practicementioning
confidence: 99%
“…We are aware of only two publications that combine SIFT‐MS and sensory analysis of beverages; mango juice, which is discussed in Section 3.4.1, and tomato juice, which is reviewed here. Mirondo and Barringer investigated improvement in flavour and viscosity in hot and cold break tomato juice (and sauce) that arises from peel removal at different stages in processing. Both juice and sauce made from the juice were analysed for volatiles (using SIFT‐MS), colour, viscosity, and by a human panel.…”
Section: Current Applications Of Sift‐ms In Food Aroma Analysismentioning
confidence: 99%
“…Examples presented here include the very recent publications on high‐throughput origin determination of Argan and olive oils. SIFT‐MS has potential to provide on‐line or high‐throughput flavour analysis correlations with sensory analysis, as illustrated by the work on Parmesan and beef On‐line monitoring to optimize product flavour during processing and avoid defects, as demonstrated by Barringer and co‐workers for tomato, cocoa, swiss cheese and coffee The European Union – and global – drive to more sustainable packaging rather than single‐use plastics will place increased demand on food researchers and manufacturers to demonstrate product integrity and safety in new packaging systems.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Lycopene is a major pigment in tomatoes that is largely responsible for the red color, and it has also important health properties [5] [6]. Since tomatoes and related products are a major source of lycopene, it is very important to consider the source of carotenoids (lycopene) in the human diet [7].…”
Section: Introductionmentioning
confidence: 99%